The role of guardians in preventing unintentional injuries among rural children: a mixed-methods study - Huang, Liheng; Luo, Dehong (Frontiers in Public Health, 2025)
BackgroundUnintentional injuries are a leading public health concern for children, particularly in rural areas of low- and middle-income countries. Guardians are important in injury prevention, yet few studies have systematically examined guardian-related factors in rural areas of China. This study investigates the association between guardian-related factors and unintentional injuries among children in Hunan Province and proposes a three-stage prevention strategy.Materials and methodsA mixed-methods approach was used. Study I adopted a quantitative design, collecting data through electronic questionnaires from 432 guardians of primary school children across five cities in Hunan Province. Logistic regression and chi-square analyses were performed using statistical software (SPSS) to assess associations between guardian-related factors and unintentional injuries among children. Study II used a qualitative approach, interviewing 30 guardians from 15 counties using a semi-structured guide. Thematic analysis was conducted using NVivo software, followed by Colaizzi’s phenomenological analysis. Findings were synthesized using the Haddon Matrix to develop three-stage preventive measures.FindingsStudy I revealed that guardians who implemented injury prevention measures were less likely to report child injuries (OR = 0.463, p < 0.05). However, most guardians lacked consistent preventive actions. Study II identified four key factors contributing to unintentional injuries among children in rural areas: hazardous environmental, inadequate safety education for guardians, children’s behaviors, and lack of regulatory and systemic safety infrastructure in rural areas.ConclusionGuardian-related factors significantly influence the prevention of unintentional injuries among rural children. By integrating quantitative and qualitative evidence within the Haddon Matrix model, this study proposes three-stage (pre-, during- and post-injury) preventive measures to reduce risks and enable a theory-driven injury prevention strategy.